ANALYTICAL STUDY OF COMMUNITY EMPOWERMENT THROUGH THE PALM OIL PLANTATION SECTOR IN HARAPAN JAYA VILLAGE BERAU REGENCY: Kajian Analitis Pemberdayaan Masyarakat Melalui Sektor Perkebunan Kelapa Sawit Di Kampung Harapan Jaya Kabupaten Berau - Alisalman, Muhamad; Mustangin, Mustangin; Lukman, A. Ismail; Abdullah, Zulkifli (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to analyze community empowerment through the oil palm plantation sector in Harapan Jaya village with indicators, planned and collective activities, improving community life, priorities for weak community groups and capacity building. The research method used is a qualitative descriptive approach. Data collection techniques through observation, interviews and documentation. The research results show that the group of ex-TKI people who first planted oil palm in Harapan Jaya village showed positive results and were followed by the community and carried out in a planned and collective manner. Oil palm plantations are able to improve people's lives with high incomes. The community is able to meet basic needs and access self-development. Oil palm plantations can be an alternative job for people in Kampung Harapan Jaya apart from the coal mining sector or other types of work that require higher educational qualifications and work experience. The government is making efforts to increase capacity by collaborating with the private sector in providing training and assistance with the aim of palm oil exports.